Magill's survey of world literature - Kellman, Steven G. 1947-; Magill, Frank N. (Frank Northen) 1907-1997; Gale Group (Pasadena, Calif. Salem Press, 2009)
Offers profiles of major writers outside the United States from all time periods, accompanied by analysis of their significant titles of fiction, drama, poetry, and nonfiction.
Volume 1. Publisher's note -- Contributors -- Complete list of contents -- Key to pronunciation -- Kobo Abe - Peter Carey -- Volume 2. Contents -- Complete list of contents -- Key to pronunciation -- Alejo Carpentier - Athol Fugard -- Volume 3. Contents -- Complete list of contents -- Key to pronunciation -- Mavis Gallant - Par Lagerkvist -- Volume 4. Contents -- Complete list of contents -- Key to pronunciation -- Selma Lagerlof - Michael Ondaatje -- Volume 5. Contents -- Complete list of contents -- Key to pronunciation -- George Orwell - Isaac Bashevis Singer -- Volume 6. Contents -- Complete list of contents -- Key to pronunciation -- Zadie Smith - Emile Zola -- Glossary of literary terms -- Category list -- Geographical list -- Title index -- Author index.
Electronic reproduction.
Keywords: Literature -- History and criticism; Literature -- Stories, plots, etc; Literature -- Bio-bibliography.; Authors -- Biography -- Dictionaries; Electronic books